The Fight against Child Poverty within the Sustainable Development Goals Framework - Marí-Klose, Pau (Acciones e Investigaciones Sociales, 2022)
The 2030 Agenda for Sustainable Development Goals (SDGs) has made a strong impact on the agenda of many multilateral entities, governments and NGOs. The fight against poverty is number 1 on the list of 17 Sustainable Development Goals. Its pre-eminent position on a global agenda of such characteristics is justified both by its relevance for promoting human well-being and social progress, and also its close association with other objectives. The experience of poverty has a universal nature, and combines various expressions of material and subjective paucity. This article looks at the dimensions of poverty contemplated in SDG 1, while focusing specifically on the fight against child poverty. The reasons are listed for affording it special attention and the magnitude of the problem is analysed both on a global scale and also in Spain. Last of all, other dimensions associated with material deprivation in childhood incorporated in other SDGs are also examined.
Keywords: Sustainable Development Goals, poverty, health, material deprivation, dignity, child labour, migration